The prognostic significance of adenosquamous carcinoma of the endometrium : a clinico-pathological analysis - Du Toit, J. P.(Johannes P.) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Med) - University of Stellenbosch, 1985.